In utero exposure to antiemetic and risk of adult-onset colorectal cancer. Issue 2 (10th March 2023) - Murphy, Caitlin C; Cirillo, Piera M; Krigbaum, Nickilou Y; Singal, Amit G; Cohn, Barbara A
Abstract: Background: Incidence rates of colorectal cancer (CRC) are increasing among adults born in and after the 1960s, implicating pregnancy-related exposures introduced at that time as risk factors. Dicyclomine, an antispasmodic used to treat irritable bowel syndrome, was initially included in Bendectin (comprising doxylamine, pyridoxine, and dicyclomine), an antiemetic prescribed during pregnancy in the 1960s. Methods: We estimated the association between in utero exposure to Bendectin and risk of CRC in offspring of the Child Health and Development Studies, a multigenerational cohort that enrolled pregnant women in Oakland, CA, between 1959 and 1966 (n = 14 507 mothers and 18 751 liveborn offspring). We reviewed prescribed medications from mothers' medical records to identify those who received Bendectin during pregnancy. Diagnoses of CRC in adult (aged ≥18 years) offspring were ascertained by linkage with the California Cancer Registry. Cox proportional hazards models were used to estimate adjusted hazard ratios, with follow-up accrued from birth through cancer diagnosis, death, or last contact. Results: Approximately 5% of offspring (n = 1014) were exposed in utero to Bendectin. Risk of CRC was higher in offspring exposed in utero (adjusted hazard ratio = 3.38, 95% confidence interval [CI] = 1.69 to 6.77) compared with unexposed offspring. Incidence rates of CRC were 30.8 (95% CI = 15.9 to 53.7) and 10.1 (95% CI = 7.9 to 12.8) per 100 000 in offspring exposed to Bendectin and unexposed, respectively. Conclusions: Higher risk of CRC in offspring exposed in utero may be driven by dicyclomine contained in the 3-part formulation of Bendectin used during the 1960s. Experimental studies are needed to clarify these findings and identify mechanisms of risk.